Analysis of community sports development based on the sports law for development through sports - Ramadhan, Muhammad Gilang; Ma'mun, Amung; Nuryadi; Juliantine, Tite (UIR Press, 2022)
This study aims to examine the implementation of community sports development policies in the context of the